Boolean Connexive Logics: Semantics and tableau approach - Jarmużek, Tomasz; Malinowski, Jacek (Logic and Logical Philosophy, 2019)
In this paper we define a new type of connexive logics which we call Boolean connexive logics. In such logics negation, conjunction and disjunction behave in the classical, Boolean way. We determine these logics through application of the relating semantics. In the final section we present a tableau approach to the discussed logics.